Peran Guru sebagai Pendidik dan Dinamika Tantangannya dalam Dunia Pendidikan Masa Kini - Umar Shodiq Rambe (Insan Zenius Ilmiah, 2025)
Teachers are the main pillars in the world of education who not only act as transmitters of material but also as character builders, learning facilitators, and agents of social change. In the context of modern education, the role of teachers has developed significantly, demanding multidimensional competencies that include pedagogical, socio-emotional, technological, and cultural abilities. This study aims to examine the role of teachers as educators comprehensively and identify the challenges faced in today's world of education. By using a qualitative approach through literature studies, data were obtained from various relevant scientific literature and analysed using content analysis techniques. The results of the study indicate that teachers have a strategic role in shaping students into individuals with character who are critical and adaptive to change. The theory of humanistic education, constructivism, and educational ecology reinforce the urgency of the role of teachers in creating an inclusive and meaningful learning environment. However, teachers also face complex internal and external pressures, such as work stress, technological demands, and student diversity. Therefore, systemic support and ongoing professional development strategies are needed to shape flexible, reflective, and progressive teachers. This research is expected to contribute to improving the quality of education by strengthening.